The Influence of the Precursor’s Deposition Order on the Properties of CZTSe Thin Films - N. Yeranyan
Cu2ZnSnSe4 (CZTSe) polycrystalline thin films have been prepared on molybdenum coated soda-lime glass substrates by DC magnetron sputtering technique. Two different deposition orders for the metallic precursors were tested, namely Mo/Cu/Zn/Sn and Mo/Zn/Cu/Sn. The influence of the precursor’s deposition order on the structural and optical parameters of the obtained thin films was studied. Structural analyses were done based on the results of XRD and stylus profilometry measurements. Optical transmittance measurements were performed in order to estimate the band gap energy of the CZTSe films. All XRD spectra show preferred growth orientation along (112)crystallographic plane. The average size of the grains calculated from XRD data is slightly bigger for the Mo/Zn/Sn/Cu sequence. The profilometry analysis shows that the average roughness and thickness of the layer were also bigger for that deposition order. Optical band gap energies derived from transmittance measurements were 1.23eV and 1.27eV for Mo/Cu/Zn/Sn and Mo/Zn/Cu/Sn, respectively.
Keywords: Physics; Materials science